2018
DOI: 10.25282/ted.375215
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy Course Requirement During Training in Different Specialities in Medicine

Abstract: Amaç: Bu çalışmada, 2017-2018 eğitim-öğretim yılında, tıp fakülte-sinde uzmanlık eğitimi alan hekimlere, kendi uzmanlık alanlarında, eğitimleri sırasında anatomi bilgisine olan gereksinimlerinin belirlenmesi amacıyla bir anket çalışması yapılmıştır. Gereç ve Yöntem:Akdeniz Üniversitesi tıp fakültesinde, 6 farklı branş-ta (Radyoloji, Plastik Cerrahi, Genel Cerrahi, Göğüs Cerrahisi Ortopedi ve Anestezi) uzmanlık eğitimi alanı asistan hekimlere, araştırmacı tarafından 6 sorudan oluşan, uzmanlık alanına anatomi eğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this survey, 96.72% of the participants stated that they needed anatomy education in their speciality and 88.7% remarked that anatomy education should be integrated into speciality education. Most of the resident physicians (62.9%) suggested that this education should be provided in the first year of residency, while 37.1% suggested the second year (13).…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, 96.72% of the participants stated that they needed anatomy education in their speciality and 88.7% remarked that anatomy education should be integrated into speciality education. Most of the resident physicians (62.9%) suggested that this education should be provided in the first year of residency, while 37.1% suggested the second year (13).…”
Section: Discussionmentioning
confidence: 99%